Qualitative Researches in Media and Communication Sciences: Theoretical Highlights and Applied Pathways - Lyadhi, Nasseraddin (ALBAHITH ALALAMI, 2020)
The debate on the methodology of media and communication research is no longer subject to the logic of the contradiction between the quantitative and the qualitative approach, nor the logic of the comparison between them. The nature of the topics presented for research, the problems they raise, the goals to be achieved from the research, and the epistemological positioning of researchers are among the critical factors that dictate the appropriate approach or methodological approaches to conduct their research. This positioning means the implicit philosophical principles upon which any researcher relies and which determine the path he/ she takes to produce scientifically approved knowledge. The method of the researcher's access to the phenomenon considered and the aim of its study are what controls his/ her epistemological position.Therefore, it can be said that we reduce the debate concerning the methodology of scientific research if we limit the difference between the quantitative and qualitative approach to saying that the first depends on numbers and the second depends on words. The difference between them is philosophical and epistemological.If we are satisfied that the qualitative research allows for a comprehensive understanding of phenomena and delves deep into the analysis of social data; and that quantitative research is a form of scrutiny of the surface of social facts, then defining the specificity of qualitative research requires approaching more of its philosophical and epistemological framework